Flexible and Adjustable Transparent Sheath Endoport combine with “two-in-one” neuroendoscopic for minimally invasive evacuation of irregular intracerebral hemorrhage - Shafiq, Zohaib; Wang, Wenju; Zhou, Long; Li, Zhiyang; Song, Ping; Zhang, Silei; Cai, Qiang (Frontiers in Neurology, 2025)
ObjectiveIrregular intracerebral hematomas (ICH), characterized by complex shapes or multi-regional involvement, pose challenges for traditional neuroendoscopy due to rigid endoport limitations. We introduce a Flexible and Adjustable Transparent Sheath Endoport (FATSE) combined with a “two-in-one” neuroendoscopic technique (stereotactic aspiration plus endoscopic evacuation) to address these challenges.MethodsIn 54 patients with irregular ICH (multi-regional, intraventricular, or width-to-length ratio < 50% on CT), we evaluated the FATSE approach. Patients were stratified into four groups by hematoma location: basal ganglia, lobar, thalamic, or intraventricular.ResultsThe mean hematoma evacuation rate was 95.0% (range 94.0–98.3%), with lobar/intraventricular hemorrhages (Group B) achieving the highest rate (95.2%). Median Glasgow Coma Scale (GCS) score improved by 5.2 points (7.2 to 12.4). There was 0% mortality, 1.9% rebleeding, and 5.6% pneumonia rates. The adjustable sheath enabled 360° cavity inspection in all cases.ConclusionThe FATSE technique offers superior evacuation rates (95.0% vs. 85–90% with rigid endoports) and improved outcomes for irregular ICH, representing a paradigm shift in minimally invasive.